Corn Cob Briquette Processing as One of the Renewable Energy in Margomulyo Village - Elsa Nuraprilia; Lailatul Mukaromah; Wasiifatul Jannah; Diva Salsabila Zahrani (Universitas Kristen Indonesia Toraja, 2024)
Margomulyo Village has a fairly large area of rice fields, plantations and dry fields where the majority of commodities are rice and corn. The existence of corn chips as a superior product and icon of village MSMEs can be drawn a line that corn cob waste is also wasteful. Briquettes are one of the waste management options where corn cobs contain high carbon materials. So that it can be used as a source of renewable energy for future needs. The purpose of making corn cob briquettes is to minimize waste disposal from corn cobs in Margomulyo Village.